Eksplorasi Kue Tradisional “Pasung” dalam Pembelajaran Matematika dengan Pendekatan Realistic Mathematics Education - Meimatul Sumandani, Arin; Saraswati, Sari; Sa’adah, Nihayatus; Ramadhani, Rahma (Program Studi Pendidikan Matematika FIP UNHASY, 2025)
The application of mathematics is often found in everyday life. So in learning mathematics, there needs to be an approach that links concepts with the real world, one of which is the Realistic Mathematics Education (RME) approach. The RME approach can be used as an effort to improve the quality of education in Indonesia. The results of mathematics education are still low because learning is only centered on teachers. The purpose of this study was to produce students' Hypothetical Learning Trajectory (HLT) on the material of spatial figures, especially the surface area of ​​cones. The method used in this study was design research, but it was only limited to the preliminary design and teaching experiment stages. The subjects of the study involved grade IX students. Data were collected through tests, documentation, and interviews. The data analysis technique used triangulation. The results showed that the HLT of the cone material included identifying “pasung” cakes, finding the elements of cones, and determining the formula for the surface area of ​​cones.